Pengetahuan Dan Kesiapan Kehidupan Berkeluarga Bagi Remaja: Studi Komparatif Di SMA, SMK DAN MA - Nining Tunggal Sri Sunarti; Isabella Rahmawati (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2022)
Background: Cases of early marriage is still high in Indonesia, including in the district ofBantul. This study aims to determine differences in knowledge and readiness of familylife for young people in SMA, SMK and MA in Bantul in the year 2015.Method: The study used observational analytic design with cross sectional approach.The study was conducted in Senior Hight Schools on the district of Bantul. Number ofsamples 3 groups, each group a total of 68 respondents. Univariate analysis usedfrequency distribution, bivariate analysis used Mann Whitney test and multivariateanalysis uses kruskal wallis.Result: The results showed that the majority of students aged 16 years and generallydo not know about the ICRS. Results of multivariate analysis with the Kruskal showedno difference in knowledge about the readiness of life for adolescents at SMA, MA andSMK (P = 0.001), and there are differences in readiness life for adolescents at SMA, MAand SMK (P = 0.002). It was concluded that there are differences in knowledge about the readiness of life for adolescents in high school, MA, and SMK and there aredifferences in readiness life for adolescents in high school, MA, and SMK. Requiredoverall effort to improve the knowledge and readiness teens about family life.Keywords: knowledge, readiness, family readiness, adolescents